Enterprise cost drivers - Anđelić Slavica; Rastić Amer; Mahmutović Meliha (Trendovi u Poslovanju)
In modern business conditions, the costs are a factor crucial to business survival and development of enterprises. Costs are relatively neglected economic category in terms of the impact they have on business success. The significance of this paper is to highlight costs as a stimulant and a factor crucial to business success, business politics and business development. The aim of this study is the importance of systematization and classification costs, which occur in economic theory and business practice. Determining cost drivers in the company has its own justification and significance, and can be useful in studying, monitoring and analyzing the costs. Different classifications are made according to different needs; they enable us to understand the essence of costs, their importance for making rational business decisions and their impact on business success.